Solution-processed ZnO nanoparticles (NPs)/CH3NH3PbI3/PTB7/MoO3/Ag inverted structure based UV–visible-Near Infrared (NIR) broadband photodetector - Upadhyay R.K.; Jit S. (My University, 2025)
This paper reports a ZnO Nanoparticles (NPs)/CH3NH3PbI3/PTB7/MoO3/Ag inverted structure based UV–visible-Near Infrared (NIR) broadband photodetector fabricated on the fluorine-doped tin oxide (FTO) coated glass substrate. ZnO NPs layer acts as the electron transport layer (ETL), CH3NH3PbI3 acts as the active layer, PTB7 acts as the hole transport layer (HTL) and MoO3 is used to optimize the recombination current in the proposed photodetector structure. Spin coating method has been used for depositing the layers of ZnO NPs, CH3NH3PbI3 and PTB7 in the proposed structure while the MoO3 layer has been grown by the thermal evaporation method. The optical measurements over 350–850 nm wavelength range give the maximum photoresponsivity, detectivity and external quantum efficiency (EQE) of ∼0.36 A/W, ∼7.8x1012 Jones and ∼83.67% under −2 V, respectively. The proposed photodetector gives a rise time and fall time of 81 ms and 75 ms, respectively. © 2022 Elsevier B.V.